Luteinizing hormone-releasing hormone agonists versus orchiectomy in the treatment of prostate cancer: A systematic review - Zhang, Xianlu; Zhang, Gejun; Wang, Jianfeng; Wang, Yanli (Frontiers in Endocrinology, 2023)
Background: Orchiectomy has been replaced by medication represented by luteinizing hormone-releasing hormone (LHRH) agonist as the first-line therapy for androgen deprivation therapy (ADT). After the wide application of LHRH agonist, the side-effects of long-term ADT were noticed. It is time to reconsider the role of medication and surgeries in the treatment of prostate cancer. Methods: Embase, Pubmed, Web of science and Cochrane library were searched for relevant trials. Quality of the studies and risk of bias were assessed by using the Newcastle-Ottawa Scale (NOS). Therapeutic and adverse effects, as well as long-term metabolic adverse effects were extracted from the selected studies. The data synthesized in meta-analyses were performed with R software (4.2.1). Risk ratio (RR) with its 95% confidence interval (CI) was calculated by combining outcome data including complete and partial response rate, progression rate, death rate and adverse effects such as hot flush and increase in pain. Descriptive analysis was performed among the prostate specific antigen (PSA), testosterone and metabolic adverse effects due to a lack of homogeneity of frailty measures. Results: 1,711 participants from 11 studies were included in our systematic review. 1,258 patients from six studies were included in the meta-analysis. Based on the meta-analysis, the therapeutic and adverse outcomes included overall response rate, complete response rate, partial response rate, stable rate, progression rate, death rate and hot flushes. No statistical significance was observed between LHRH agonists and orchiectomy. Compared with surgery, LHRH agonist elevated the risk of the increase in pain. In descriptive analysis, it was shown that the therapeutic effects between PSA and testosterone also showed no significant difference. Both groups had lipid and glucose metabolic disorders, and a few studies reported worse lipid metabolic performance in orchiectomy group and worse insulin resistance in LHRH agonist group. Conclusion: We found that the therapeutic outcomes were similar between the two options. The results of lipid and glucose metabolic abnormality were controversial in existing studies. The direct comparison studies on metabolic adverse effects should be performed in the future. The therapeutic, metabolic, psychological and economical effects should be considered before applying ADT methods.